Programming ArcGIS 10.1 with Python Cookbook. - Pimpler, Eric (Packt Pub., 2013)
This book is written in a helpful, practical style with numerous hands-on recipes and chapters to help you save time and effort by using Python to power ArcGIS to create shortcuts, scripts, tools, and customizations.""Programming ArcGIS 10.1 with Python Cookbook"" is written for GIS professionals who wish to revolutionize their ArcGIS workflow with Python. Basic Python or programming knowledge is essential.